2021
DOI: 10.3389/fpls.2021.645055
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Characterization and Validation of Chromosome-Specific Highly Polymorphic SSR Markers From Pomegranate (Punica granatum L.) cv. Tunisia Genome

Abstract: The simple sequence repeat (SSR) survey of ‘Tunisia’ genome (296.85 Mb) identified a total of 365,279 perfect SSRs spanning eight chromosomes, with a mean marker density of 1,230.6 SSRs/Mb. We found a positive trend in chromosome length and the SSR abundance as marker density enhanced with a shorter chromosome length. The highest number of SSRs (60,708) was mined from chromosome 1 (55.56 Mb), whereas the highest marker density (1,294.62 SSRs/Mb) was recorded for the shortest chromosome 8 (27.99 Mb). Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 63 publications
7
21
1
Order By: Relevance
“…A total of 13,335 SSRs were successfully identified, where maximum relative abundance and density were obtained for di-nucleotides (9.65 loci Mb -1 ; 140.18 bp Mb -1 ) followed by tri-, tetraand penta-nucleotides. It revealed that most of the nongenic region contains a large set of di-nucleotides repeats, which is similar to other taxon studies (Karaoglu et al 2005;Patil et al 2021;Sigang et al 2021;Zhu et al 2021). The SSR repeat analysis revealed that di-and tri-nucleotide repeats were almost ubiquitous in the genome, and these classes were further dominated by repeat motifs AG/CT and AAT/CTT, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…A total of 13,335 SSRs were successfully identified, where maximum relative abundance and density were obtained for di-nucleotides (9.65 loci Mb -1 ; 140.18 bp Mb -1 ) followed by tri-, tetraand penta-nucleotides. It revealed that most of the nongenic region contains a large set of di-nucleotides repeats, which is similar to other taxon studies (Karaoglu et al 2005;Patil et al 2021;Sigang et al 2021;Zhu et al 2021). The SSR repeat analysis revealed that di-and tri-nucleotide repeats were almost ubiquitous in the genome, and these classes were further dominated by repeat motifs AG/CT and AAT/CTT, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…Six classes of perfect SSRs were evaluated (from mono-to hexanucleotide) for their abundance in the assembled genome. Dinucleotides were the most abundant, in accordance with what has been previously reported in literature [30][31][32][33][34][35][36][37][38][39], representing 60.2% of the identified SSRs. Trinucleotides were the second most abundant class (23.7%), followed by tetranucleotides (6.8%).…”
Section: The Ssr Content Of the Poppy Anemone Draft Genomesupporting
confidence: 91%
“…Pomegranate ( Punica granatum L.) is one of the oldest edible fruit crops belonging to the family Lythraceae ( Dandachi et al, 2017 ). It is believed to have originated from Iran and is widely grown in drier parts of the world, i.e., Southeast Asia, India, Iran, China, Japan, United States (California), Israel, Spain, Turkey, and Israel ( Yan et al, 2019a ; Patil et al, 2020 , 2021 ; Singh et al, 2020a ). Being a native of central Asia that is from Iran to Western Himalayas in India, later, it was domesticated to many other parts of the world ( Holland et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%